Peran Kepuasan Dalam Memediasi Pengaruh Kualitas Layanan Terhadap Loyalitas Nasabah - Trisnayani, I Dewa Ayu Mas Dewi; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
In the banking world, together with a valuable service owned products, this means that the service is received in the same view of the customer with a product in other industries. This research was conducted at the Regional Development Bank Bali Denpasar Branch Office in Cambodia. With a sample of 126 persons were used as the method of probability sampling. The analysis technique used is simple and the regression method of Coefficient Product (Sobel test). The results of this study indicate that the quality of service results positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction and a significant positive effect on customer loyalty. Finally, the satisfaction mediates the effect of service quality on customer loyalty. Keywords: quality of service, customer satisfaction, customer loyalty.
Keywords: quality of service, customer satisfaction, customer loyalty.